Some fixed point theorems via γ-ψS -contractions on S-metric spaces - Tas, Nihal; Kaplan, Elif (Vojnotehnički glasnik / Military Technical Courier, 2025)
In this paper, the authors introduce generalized contractive conditions on $%S $-metric spaces, aiming to expand the existing theory of fixed points insuch spaces. They apply these new contractive conditions to prove severalfixed-point theorems, including integral-type fixed-point results.Additionally, they employ a geometric approach to derive new fixed-circletheorems on $S$-metric spaces, providing necessary examples to illustratethese results. In the concluding section, the paper highlights thesignificance of these findings, particularly in the context of activationfunctions, emphasizing the potential applications of their work in areaslike computational mathematics and neural networks.
Keywords: $S$-metric space; contractive condition; fixed point; fixed circle